From the experience of research of the national-cultural specificity of language consciousness: associative norms of noun ‘steppe’ in the Kazakhstan language environment - Grigoryeva, Irina (Przegląd Wschodnioeuropejski, 2018)
The article is devoted to the study of associative field of the word using the method of experiment. The paper presents a brief review of the definitions of concepts such as: free associative experiment, association, content analysis. The article attempts to analyze the results of the free associative experiment, associative field study of steppe. The factual material for illustration of the main provisions was the direct lexical association of the respondents. The experimental data allow us to observe mental stereotypes of society, to reveal its cultural memory, modern values verbalized in associations. The following methods were used in the research: questionnaire survey, descriptive, generalization, systematization, observation, content analysis.